The thermodynamic principles as the theoretical basis of fair remuneration - Dobija, MieczysÅ‚aw; Renkas, Jurij (International Journal of Physical Research, 2020)
Thermodynamics is the key to solving many economic problems. Since the human body is driven by heat engines, there is a loss of energy source. Measuring this loss means it is possible to indicate the size of a fair wage. Another version of the second principle justifies the amount of depreciation of real assets, such as machinery and equipment. A significant purpose of the article is to indicate that the category of capital cannot be understood without knowing the first and second principle of thermodynamics. The main aim is to present the theory of equitable remuneration developed using the second principle of thermodynamics and the discovered economic constant. Theoretical research leads to the creation of a model of capital and a model of fair pay with the understanding of the existence of an economic constant quantifying the action of natural forces on capital growth. Empirical research estimates the size of the constant and verifies the fairness of remuneration. The research reveals the existence of an economic constant necessary in capital theory, especially in the field of remuneration for work. Models for measuring human capital of employees and formulas enabling calculation of fair remuneration and its updating are presented. Additionally, using the entropic version of the second principle, the depreciation amounts of fixed assets are determined. The main conclusion of the presented research and the formulated theory is that thermodynamics is essential for the correct understanding of the category of capital defining as the abstract ability to perform work.Â Â